EFFECT OF ORGANIC FERTILIZERS ON K- AVAILABILITY FOR CORN PLANT Zea mays L. - M. Al-Obaidi (Mesopotamia Journal of Agriculture)
The work described in this research was an attempt to through some light on the factors which govern the effect of organic fertilizers (urea, sheep manure and urea + sheep manure) and methods of K- application (surface and sub surface. application)on the K availability in calcareous soil , growth and yield of corn plants. Results revealed that the addition of organic fertilizers significantly increased dry matter and grain yield as compared to that of urea mixed with sheep manure treatment . Sub surface application of K gave ahigher growth , grain yield ,dry matter, potassium uptake, and available potassium in soil (136, 70, 84and 55%), respectively.